CLA for More Effective Development Programs (video) (USAID, 2014)
This presentation features USAID/PPL's Stacey Young discussing the his tory of learning at USAID; how collaborating, learning, and adapting ( CLA) can enhance development outcomes, and the role of implementing pa rtners in supporting this vision.